Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

A Dominant Founder Lineage Has Possible Fitness Costs for the Endangered Mexican Grey Wolf - Yeraldi Loera; Manisha Khakoo; Emily Krueckeberg; Ingrid G. Nilsson; Zehao Wu; Maggie Dwire; Jennifer Adams; Lisette Waits; John K. Oakleaf; Mariel L. Campbell; Jonathan L. Dunnum; Joseph A. Cook; et al. (Molecular Ecology, 2026)
The Mexican grey wolf ( Canis lupus baileyi ) is an endangered and genetically distinct subspecies of grey wolf adapted to the warm climates of the southwestern United States and Mexico. Following centuries of eradication efforts, Mexican grey wolves were protected under the Endangered Species Act in 1976, prompting an international ex situ breeding program to preserve their genetic legacy. Seven remnant wolves founded the three distinct lineages of this program: McBride, Ghost Ranch, and Aragón. However, concerns of rising inbreeding levels motivated the implementation of inter‐lineage pairings to decelerate genetic erosion. To evaluate the genetic health of the ex situ managed population, we analysed genome‐wide variation across several generations of breeding wolves and their descendants ( n = 179). Despite ongoing conservation interventions, we found a sharp decline in effective population size over the past 50 generations. However, estimates of inbreeding diminished over time following the inter‐lineage pairings, reflecting efficient pedigree management or potential fitness costs of inbreeding depression, as higher levels of inbreeding and autozygosity were associated with reduced lifespan and reproductive performance. Increasing contributions of Ghost Ranch and Aragón ancestry also aided in reducing levels of inbreeding observed in the more genetically distinct McBride lineage. These findings highlight the challenges of maintaining genetic diversity in bottlenecked populations, reveal fine‐scale patterns of inbreeding within the pedigree and underscore the urgent need to preserve genetic contributions from all founder lineages. Genomic insights from this study can guide breeding strategies to reduce kinship, balance ancestry and mitigate inbreeding depression, safeguarding the evolutionary legacy and the long‐term persistence of the Mexican grey wolf.

Associations of endocrine disrupting chemical biomarkers and their mixture with vitamin D biomarker concentrations in childhood: The HOME Study - Katherine M. Marquess; Jordan R. Kuiper; Taylor M. Etzel; Bruce P. Lanphear; Andrew N. Hoofnagle; Antonia M. Calafat; Julianne Cook Botelho; Maria Ospina; Andreas Sjodin; Lesliam Quirós-Alcalá; Kim M. Cecil; Aimin Chen; et al. (Environmental Research, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Time since HIV diagnosis is linked to amnestic mild cognitive impairment (MCI) in older adults with HIV - Jason S. DeFelice; Mark K. Britton; Yancheng Li; Eric C. Porges; Gladys E. Ibañez; Charurut Somboonwit; Robert L. Cook; Ronald A. Cohen; Joseph M. Gullett (Journal of NeuroVirology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Correction to: Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Mid-to Late Holocene East Antarctic ice-core tephrochronology: Implications for reconstructing volcanic eruptions and assessing their climatic impacts over the last 5,500 years - Peter M. Abbott; Joseph R. McConnell; Nathan J. Chellman; Sepp Kipfstuhl; Maria Hörhold; Johannes Freitag; Eliza Cook; William Hutchison; Michael Sigl (Quaternary Science Reviews, 2024)

The distinctive weathering crust habitat of a High Arctic glacier comprises discrete microbial micro‐habitats - Sara M. E. Rassner; Joseph M. Cook; Andrew C. Mitchell; Ian T. Stevens; Tristram D. L. Irvine‐Fynn; Andrew J. Hodson; Arwyn Edwards (Environmental Microbiology, 2024)
Sunlight penetrates the ice surfaces of glaciers and ice sheets, forming a water‐bearing porous ice matrix known as the weathering crust. This crust is home to a significant microbial community. Despite the potential implications of microbial processes in the weathering crust for glacial melting, biogeochemical cycles, and downstream ecosystems, there have been few explorations of its microbial communities. In our study, we used 16S rRNA gene sequencing and shotgun metagenomics of a Svalbard glacier surface catchment to characterise the microbial communities within the weathering crust, their origins and destinies, and the functional potential of the weathering crust metagenome. Our findings reveal that the bacterial community in the weathering crust is distinct from those in upstream and downstream habitats. However, it comprises two separate micro‐habitats, each with different taxa and functional categories. The interstitial porewater is dominated by Polaromonas , influenced by the transfer of snowmelt, and exported via meltwater channels. In contrast, the ice matrix is dominated by Hymenobacter , and its metagenome exhibits a diverse range of functional adaptations. Given that the global weathering crust area and the subsequent release of microbes from it are strongly responsive to climate projections for the rest of the century, our results underscore the pressing need to integrate the microbiome of the weathering crust with other communities and processes in glacial ecosystems.

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Ancient bears provide insights into Pleistocene ice age refugia in Southeast Alaska - Flavio Augusto da Silva Coelho; Stephanie Gill; Crystal M. Tomlin; Marilena Papavassiliou; Sean D. Farley; Joseph A. Cook; Sarah A. Sonsthagen; George K. Sage; Timothy H. Heaton; Sandra L. Talbot; Charlotte Lindqvist (Molecular Ecology, 2023)
During the Late Pleistocene, major parts of North America were periodically covered by ice sheets. However, there are still questions about whether ice‐free refugia were present in the Alexander Archipelago along the Southeast (SE) Alaska coast during the last glacial maximum (LGM). Numerous subfossils have been recovered from caves in SE Alaska, including American black ( Ursus americanus ) and brown ( U. arctos ) bears, which today are found in the Alexander Archipelago but are genetically distinct from mainland bear populations. Hence, these bear species offer an ideal system to investigate long‐term occupation, potential refugial survival and lineage turnover. Here, we present genetic analyses based on 99 new complete mitochondrial genomes from ancient and modern brown and black bears spanning the last ~45,000 years. Black bears form two SE Alaskan subclades, one preglacial and another postglacial, that diverged >100,000 years ago. All postglacial ancient brown bears are closely related to modern brown bears in the archipelago, while a single preglacial brown bear is found in a distantly related clade. A hiatus in the bear subfossil record around the LGM and the deep split of their pre‐ and postglacial subclades fail to support a hypothesis of continuous occupancy in SE Alaska throughout the LGM for either species. Our results are consistent with an absence of refugia along the SE Alaska coast, but indicate that vegetation quickly expanded after deglaciation, allowing bears to recolonize the area after a short‐lived LGM peak.

Late Cenozoic history and the role of Beringia in assembling a Holarctic cestode species complex - Kurt E. Galbreath; Arseny A. Makarikov; Kayce C. Bell; Stephen E. Greiman; Julie M. Allen; Genevieve M.S. Haas; Chenhong Li; Joseph A. Cook; Eric P. Hoberg (Molecular Phylogenetics and Evolution, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Taxon pulse dynamics, episodic dispersal and host colonization across Beringia drive diversification of a Holarctic tapeworm assemblage - Genevieve M. S. Haas; Eric P. Hoberg; Joseph A. Cook; Heikki Henttonen; Arseny A. Makarikov; Sarah R. Gallagher; Nikolai E. Dokuchaev; Kurt E. Galbreath (Journal of Biogeography, 2020)
Aim We test the predictions of the Stockholm Paradigm, a synthesis of eco‐evolutionary theory explaining the nature of faunal assembly, host range and parasite diversification. Faunal diversification and assembly, manifested in patterns of host colonization, co‐adaptation and parasite speciation, are predicted to emerge as a consequence of alternating episodes of ecological disruption and stability. Specifically, for a diverse cestode genus ( Arostrilepis ), we evaluate the number and direction of Pleistocene dispersal events across Beringia, the number and relative timing of host colonization events and the relationship between host and parasite biogeographic histories and associations through time. Location Beringia and adjacent temperate to arctic biomes in North America and Eurasia. Taxon Arostrilepis (Cyclophyllidea: Hymenolepididae) and its rodent hosts. Methods Multi‐locus phylogenetic reconstruction and biogeographic ancestral range estimation. Results Arostrilepis lineages crossed Beringia eastward into North America a minimum of four times and westward into Asia twice in association with temporally disjunct geographic expansions of three major tribes of cricetid rodents (Arvicolini, Myodini, Lemmini). Inferences of ancestral host associations support at least nine instances of host colonization involving shifts from one rodent tribe or family to another. Several previously unrecognized lineages of Arostrilepis are revealed. Main conclusions Consistent with expectations of the Stockholm Paradigm, episodes of intercontinental dispersal were both frequent in the history of Arostrilepis and preceded a majority of inferred host‐colonization events. Events of historical geographic expansion created numerous opportunities for development of novel host–parasite associations through ecological fitting, as parasites tracked historically conserved resources available across diverse host taxa. Beringia played a major role in shaping rodent/parasite assemblages by mediating dispersal between the northern continents during glacial episodes of the Pleistocene, rather than by serving as a zone of refugial isolation.

We need both natural and energy solutions to stabilize our climate - Bronson W. Griscom; Guy Lomax; Timm Kroeger; Joseph E. Fargione; Justin Adams; Lucy Almond; Deborah Bossio; Susan C. Cook‐Patton; Peter W. Ellis; Christina M. Kennedy; Joseph Kiesecker (Global Change Biology, 2019)

Metabolome‐mediated biocryomorphic evolution promotes carbon fixation in G reenlandic cryoconite holes - Joseph M. Cook; Arwyn Edwards; Mark Bulling; Luis A. J. Mur; Sophie Cook; Jarishma K. Gokul; Karen A. Cameron; Michael Sweet; Tristram D. L. Irvine‐Fynn (Environmental Microbiology, 2016)
Summary Microbial photoautotrophs on glaciers engineer the formation of granular microbial‐mineral aggregates termed cryoconite which accelerate ice melt, creating quasi‐cylindrical pits called ‘cryoconite holes’. These act as biogeochemical reactors on the ice surface and provide habitats for remarkably active and diverse microbiota. Evolution of cryoconite holes towards an equilibrium depth is well known, yet interactions between microbial activity and hole morphology are currently weakly addressed. Here, we experimentally perturbed the depths and diameters of cryoconite holes on the Greenland Ice Sheet. Cryoconite holes responded by sensitively adjusting their shapes in three dimensions (‘biocryomorphic evolution’) thus maintaining favourable conditions for net autotrophy at the hole floors. Non‐targeted metabolomics reveals concomitant shifts in cyclic AMP and fucose metabolism consistent with phototaxis and extracellular polymer synthesis indicating metabolomic‐level granular changes in response to perturbation. We present a conceptual model explaining this process and suggest that it results in remarkably robust net autotrophy on the Greenland Ice Sheet. We also describe observations of cryoconite migrating away from shade, implying a degree of self‐regulation of carbon budgets over mesoscales. Since cryoconite is a microbe‐mineral aggregate, it appears that microbial processes themselves form and maintain stable autotrophic habitats on the surface of the Greenland ice sheet.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2014)
HIV-associated neurocognitive disorder (HAND), characterized by a wide spectrum of behavioral, cognitive, and motor dysfunctions, continues to affect approximately 50 % of HIV(+) patients despite the success of combination antiretroviral drug therapy (cART) in the periphery. Of note, potential toxicity of antiretroviral drugs in the central nervous system (CNS) remains remarkably underexplored and may contribute to the persistence of HAND in the cART era. Previous studies have shown antiretrovirals (ARVs) to be neurotoxic in the peripheral nervous system in vivo and in peripheral neurons in vitro. Alterations in lipid and protein metabolism, mitochondrial damage, and oxidative stress all play a role in peripheral ARV neurotoxicity. We hypothesized that ARVs also induce cellular stresses in the CNS, ultimately leading to neuronal damage and contributing to the changing clinical and pathological picture seen in HIV-positive patients in the cART era. In this report, we show that ARVs are neurotoxic in the CNS in both pigtail macaques and rats in vivo. Furthermore, in vitro, ARVs lead to accumulation of reactive oxygen species (ROS), and ultimately induction of neuronal damage and death. Whereas ARVs alone caused some activation of the endogenous antioxidant response in vitro, augmentation of this response by a fumaric acid ester, monomethyl fumarate (MMF), blocked ARV-induced ROS generation, and neuronal damage/death. These findings implicate oxidative stress as a contributor to the underlying mechanisms of ARV-induced neurotoxicity and will provide an access point for adjunctive therapies to complement ARV therapy and reduce neurotoxicity in this patient population.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Biogeography of the Australian monsoon tropics - D. M. J. S. Bowman; G. K. Brown; M. F. Braby; J. R. Brown; L. G. Cook; M. D. Crisp; F. Ford; S. Haberle; J. Hughes; Y. Isagi; L. Joseph; J. McBride; et al. (Journal of Biogeography, 2010)
Aim This paper reviews the biogeography of the Australian monsoon tropical biome to highlight general patterns in the distribution of a range of organisms and their environmental correlates and evolutionary history, as well as to identify knowledge gaps. Location Northern Australia, Australian Monsoon Tropics (AMT). The AMT is defined by areas that receive more than 85% of rainfall between November and April. Methods Literature is summarized, including the origin of the monsoon climate, present‐day environment, biota and habitat types, and phylogenetic and geographical relationships of selected organisms. Results Some species are widespread throughout the AMT while others are narrow‐range endemics. Such contrasting distributions correspond to present‐day climates, hydrologies (particularly floodplains), geological features (such as sandstone plateaux), fire regimes, and vegetation types (ranging from rain forest to savanna). Biogeographical and phylogenetic studies of terrestrial plants (e.g. eucalypts) and animals (vertebrates and invertebrates) suggest that distinct bioregions within the AMT reflect the aggregated effects of landscape and environmental history, although more research is required to determine and refine the boundaries of biogeographical zones within the AMT. Phylogenetic analyses of aquatic organisms (fishes and prawns) suggest histories of associations with drainage systems, dispersal barriers, links to New Guinea, and the existence of Lake Carpentaria, now submerged by the Gulf of Carpentaria. Complex adaptations to the landscape and climate in the AMT are illustrated by a number of species. Main conclusions The Australian monsoon is a component of a single global climate system, characterized by a dominant equator‐spanning Hadley cell. Evidence of hot, seasonally moist climates dates back to the Late Eocene, implying that certain endemic elements of the AMT biota have a long history. Vicariant differentiation is inferred to have separated the Kimberley and Arnhem Land bioregions from Cape York Peninsula/northern Queensland. Such older patterns are overlaid by younger events, including dispersal from Southeast Asia, and range expansions and contractions. Future palaeoecological and phylogenetic investigations will illuminate the evolution of the AMT biome. Understanding the biogeography of the AMT is essential to provide a framework for ecological studies and the sustainable development of the region.

Temporal resolution of the Florida manatee (Trichechus manatus latirostris) auditory system - David A. Mann; Debborah E. Colbert; Joseph C. Gaspard; Brandon M. Casper; Mandy L. H. Cook; Roger L. Reep; Gordon B. Bauer (Journal of Comparative Physiology A, 2005)

Postglacial expansion of the southern red‐backed vole ( Clethrionomys gapperi ) in North America - AMY M. RUNCK; JOSEPH A. COOK (Molecular Ecology, 2005)
Dynamic climatic oscillations of the Pleistocene dramatically changed the distributions of high latitude species. Molecular investigations of a variety of organisms show that processes of postglacial colonization of boreal regions were more complex than initially thought. Phylogeographical and coalescent analyses were conducted on partial sequences of the cytochrome b gene (600 bp) from 64 individuals of Clethrionomys gapperi from North Carolina, Pennsylvania, Minnesota, Idaho, Washington, British Columbia, Northwest Territories, and Alaska to test hypotheses relating to Pleistocene refugia and postglacial colonization routes. Three divergent clades (east, west, central) were identified with highest net divergence ( d A = 5.2%) between the eastern and western clades. Populations from the recently deglaciated higher latitudes of Canada and Alaska are closely related to lower latitude populations of the central clade ( d A = 1.2%) suggesting recent expansion from this midwestern region. No representatives from the east or west clade were found at latitudes higher than 50°N, indicating that postglacial colonization occurred through a midcontinental route. The high latitude population from the Northwest Territories exhibited demographic patterns and genetic diversity consistent with a stable noncolonizing population. This population is found near the Mackenzie range, where the two continental ice sheets were believed to have coalesced. Molecular variation observed in this population may be the result of leading edge population diversifying in the continental corridor or may reflect the signal of a high latitude refugial population.